(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
This article discusses the topic of modeling switched reluctance motors (SRM) and the symbiosis that occurs between the converter modeling, control and application. This article will propose some considerations in relation to the motor-drive. In addition, it will establish a comprehensive modeling using a linear or nonlinear issue regarding the application. Finally, this article explains the use and operation of multiple-motor drive models which have been entirely developed using Matlab-Simulink.